Yānasampannathammānusō̜n - Būa Yānnasampannō (Wat Pā Bān Tāt, 2011)
On Buddhism and biography of Phra Mahā Boowa Ñāṇasampanno, a Thai monastic; volume brought out for his cremation at Wat Pa Ban Tat on March 5th, 2011
Zur Trauerfeier von Būa Yānnasampannō publiziert
Keywords: Boowa Ñāṇasampanno; Buddhism; Cremation Volume